Implementasi Pengaturan Pengelolaan Sampah Di Kabupaten Buleleng - I Nyoman Adi Susila; I Nyoman Ariyoga (PARIKSA: Jurnal Hukum Agama Hindu, 2021)
The Government of Buleleng Regency has established a regional regulation on garbage management, which is contained in the regional regulation of Buleleng Regency No.1 of 2013. In addition, to the government as a rule maker and implementation of these regional regulations, the community has also a role to play and participate in garbage management. Garbage is a problem that must be faced by the community because garbage is a form of environmental pollution, where human activity becomes an external factor causing foreign substances that was not initially present in the living area to enter the environment. Subsequently, two problem formulations were formulated, namely: (1) regulation of garbage management in Buleleng Regency and (2) programs carried out by the Buleleng Regency government in efforts to manage garbage in its area. In this regard, it can be concluded that the regulation of garbage management in Buleleng Regency is based on the regional regulation of Buleleng Regency No.1 of 2013 concerning Garbage Management in Buleleng Regency. This is based on the condition of Buleleng Regency as an autonomous region. One of the programs carried out by the Buleleng Regency government in efforts to manage garbage in its area is by building a garbage bank, where every garbage produced by the people of Buleleng Regency is collected and managed by a garbage bank so that it has economic value.